Scalable high-affinity stabilization of magnetic iron oxide nanostructures by a biocompatible antifouling homopolymer - Luongo,G; Perez,JE; Kosel,J; Georgiou,TK; Regoutz,A; Payne,DJ; Stevens,MM; Porter,AE; Dunlop,IE (ACS Applied Materials and Interfaces, 2017)
Iron oxide nanostructures have been widely developed for biomedical applications, due to their magnetic properties and biocompatibility. In clinical application, the stabilization of these nanostructures against aggregation and non-specific interactions is typically achieved using weakly anchored polysaccharides, with better-defined and more strongly anchored synthetic polymers not commercially adopted due to complexity of synthesis and use. Here, we show for the first time stabilization and biocompatibilization of iron oxide nanoparticles by a synthetic homopolymer with strong surface anchoring and a history of clinical use in other applications, poly(2-methacryloyloxyethy phosphorylcholine) (poly(MPC)). For the commercially important case of spherical particles, binding of poly(MPC) to iron oxide surfaces and highly effective individualization of magnetite nanoparticles (20 nm) are demonstrated. Next-generation high-aspect ratio nanowires (both magnetite/maghemite and core-shell iron/iron oxide) are furthermore stabilized by poly(MPC)-coating, with nanowire cytotoxicity at large concentrations significantly reduced. The synthesis approach is exploited to incorporate functionality into the poly(MPC) chain is demonstrated by random copolymerization with an alkyne-containing monomer for click-chemistry. Taking these results together, poly(MPC) homopolymers and random copolymers offer a significant improvement over current iron oxide nanoformulations, combining straightforward synthesis, strong surface-anchoring and well-defined molecular weight.